ANALISIS HOTSPOT DAN VALIDASI PENGUKURAN THERMOVISI PADA PERALATAN GARDU INDUK TRANSMISI. - Rival Septian; Yasin Mohamad; Taufiq Ismail Yusuf; Lanto Mohamad Kamil Amali (Journal Of Renewable Energy Engineering, 2026)
Thermal monitoring of transmission equipment is an essential component in maintaining the reliability, continuity, and efficiency of electric power systems, particularly for substation equipment that operates continuously under high loading and open-environment exposure. This study aims to analyze hotspot phenomena while simultaneously evaluating the reliability of thermovision measurements on Main Transmission Equipment at Bay GT of the Anggrek Substation. The research employed a quantitative descriptive approach through direct field measurements using thermovision under peak-load conditions. The results show that Bay GT 1 exhibited higher thermal characteristics than Bay GT 2, with maximum clamp temperatures of 33.2 °C and 27.6 °C, respectively. Several points in both bays recorded ΔT values greater than 10 °C, indicating the presence of localized thermal anomalies. Emissivity values ranged from 0.47440 to 0.53377 for Bay GT 1 and from 0.51073 to 0.56425 for Bay GT 2, suggesting that the material condition remained relatively stable. Validation results further showed precision levels of 0.6% and 0.5%, with corresponding accuracy values of 98.7% and 91.9%.